In vitro and in vivo safety studies indicate that R15, a synthetic polyarginine peptide, could safely reverse the effects of unfractionated heparin. Issue 9 (12th August 2021) - Li, Tong; Meng, Zhiyun; Zhu, Xiaoxia; Gan, Hui; Gu, Ruolan; Wu, Zhuona; Liu, Taoyun; Han, Peng; Gao, Jiarui; Han, Su; Dou, Guifang
Abstract : Unfractionated heparin (UFH) is an anionic glycosaminoglycan that is widely used to prevent blood clotting. However, in certain cases, unwanted side effects can require it to be neutralized. Protamine sulfate (PS), a basic peptide rich in arginine, is the only approved antagonist for UFH neutralization. Many adverse reactions occur with the clinical application of PS, including systemic hypotension, pulmonary hypertension, and anaphylaxis. We previously described R15, a linear peptide composed of 15 arginine molecules, as a potential UFH antagonist. In this study, the in‐depth safety of R15 was explored to reveal its merits and associated risks in comparison with PS. In vitro safety studies investigated the interactions of R15 with erythrocytes, fibrin, complement, and rat plasma. In vivo safety studies explored potential toxicity and immunogenicity of R15 and the UFH–R15 complex. Results showed that both PS and R15 can induce erythrocyte aggregation, thicken fibrin fibers, activate complement, and cause anticoagulation in a concentration‐dependent manner. However, those influences weakened in whole blood or in live animals and were avoided when R15 was in a complex with UFH. We found dramatically enhanced complement activation when there was excess UFH in analyses involving UFH–PS complexes, and a slight increase in those involving UFH–R15 complexes. Within 2 h, R15 was degraded in rat plasma in vitro, whereas PS was not. Enhanced creatinine was found after a single intravenous injection of PS or R15 (900 U·kg −1, body weight), suggesting possible abnormal renal function. The UFH–PS complex, but not the UFH–R15 complex, exhibited obvious immunogenicity. In conclusion, R15 is nonimmunogenic and potentially safe at a therapeutic dose to reverse the effects of UFH. Abstract : Safety studies of R15, a new heparin antagonist, were investigated in comparison with PS (protamine sulfate). R15 was degradable in plasma of rats within 2 h, whereas PS was not. Dramatically enhanced complement activation was observed for UFH–PS complex with excess UFH (unfractionated heparin). UFH–PS complex possessed immunogenicity that was completely absent for the UFH–R15 complex.